Dayside magnetospheric ULF wave frequency modulated by a solar wind dynamic pressure negative impulse. Issue 2 (10th February 2017) - Shen, X. C.; Shi, Q. Q.; Zong, Q.‐G.; Tian, A. M.; Nowada, M.; Sun, W. J.; Zhao, H. Y.; Hudson, M. K.; Wang, H. Z.; Fu, S. Y.; Pu, Z. Y.
Abstract: Ultralow frequency (ULF) waves play an important role in the transport of the solar wind energy to the magnetosphere. In this paper, we present a ULF wave event in the dayside magnetosphere which shows a sudden decrease in frequency from 3.1 to 2.3 mHz around 0756 UT on 11 January 2010, when a solar wind dynamic pressure drop (from ∼5 to ∼2 nPa) was observed simultaneously. The wave exits globally. The phase differences between electric and magnetic fields indicate that the compressional mode wave is standing before and after the wave frequency decrease. This result suggests that the ULF wave should be associated with a cavity mode and the frequency decrease might be induced by the change of the cavity size. A theoretical calculation was made to estimate the cavity mode frequency. The calculated wave frequency before/after the negative impulse is 3.8/2.6 mHz, which is consistent with the observations. Key Points: When a negative P sw impulse impacted on magnetosphere, ULF wave frequency sudden decrease was observed Compressional mode waves are standing before and after the negative P sw pulse arrival Frequency decrease could be modulated by the cavity size